Simone Fattal - works and days - Fattal, Simone 1942-; Eleey, Peter ca. 20. Jh; Arndt, Jaclyn (MoMA PS1, 2019)
Published for the artist's first solo exhibition at an American museum, this catalog highlights a selection of the more than 200 works by Paris- and California-based Lebanese artist and publisher Simone Fattal (born 1942). Over the past 40 years, Fattal has made work encompassing abstract and figurative ceramics, bronzes, paintings, watercolors and collages. These works draw from a range of sources including war narratives, landscape painting, ancient history, mythology and Sufi poetry to explore the impact of displacement as well as the politics of archeology and excavation. The first catalog on her work to be published in the United States, Works and Days features a selection of color plates tracing the arc of Fattal's career from 1969 to the present, as well as an essay by Ruba Katrib, the exhibition curator. Exhibition: MoMA PS1, New York, USA (31.03.-02.09.2019)
Impressum: Published on the occasion of the exhibition "Simone Fattal: Works and Days", curated by Ruba Katrib and organized by MoMA PS1, Long Island City, New York, March 31-September 2, 2019
Keywords: Fattal, Simone -- 1942-; Geschichte 1969-2018; Ölmalerei; Plastik; Fattal, Simone / Exhibitions; Sculpture / Lebanon / Exhibitions; Sculpture; Lebanon; Exhibition catalogs; Ausstellungskatalog -- PS 1 Contemporary Art Center -- 31.03.2019-02.09.2019 -- Long Island City, NY; Bildband